Factors Affecting Readmission in Hospitalized Patients with Chronic Kidney Disease: a Single Center Study - Wagle, Abhishesh; Sigdel, Mahesh R (Journal of Institute of Medicine Nepal, 2022)
Introduction: Chronic Kidney disease (CKD) in itself and the associated comorbidities together put the patients at increased risk of hospitalization. We aimed to study the factors associated with hospital readmission within 30 days of discharge in hospitalized patients with CKD. Methods: This was a single center descriptive observational study conducted in Tribhuvan University Teaching Hospital (TUTH), Kathmandu. Hospitalized CKD patients were evaluated for sociodemographic parameters, clinical profile and laboratory parameters; they were asked over the phone after 30 days of discharge if they had repeat hospitalization. Readmission rates were calculated and factors at admission associated with repeat hospitalization were analyzed. Results: Out of 337 CKD patients 307 could be contacted. Fifty patients (16.28%) needed readmission. Readmission rate was higher in patients older than 75 years and between ages 25 to 50. Patients who were undergoing dialysis at TUTH (OR 3.324 CI 1.239-8.917, p=0.017), who belonged to Newari community (OR 2.85 CI 1.17-6.9, p=0.020) and those from Kathmandu valley (1.94,CI 0.94-3.99) had higher odds of readmission. Hypertension, diabetes mellitus and tuberculosis as a comorbidity had increased odds of readmission of (1.51,CI 0.60-3.77), (1.48, CI 0.79-2.76), (1.569,CI 0.441-4.468) respectively. Hemoglobin less than 9 gm/dl and serum albumin less than 35 gm/l had higher odds of readmission of (1.109 95% CI 0.605-2.033) and (1.877,95%CI 0.869-4.054) respectively. Conclusion: Overall 30 day readmission rate of Hospitalized CKD patients was 16.28%. Elderlies, those with medical comorbiditites, anemic and hypoalbuminemic patients tended to have increased odds of readmission.